Can Women's Self-Help Groups Contribute to Sustainable Development? Evidence of Capability Changes from Northern India - Anand, Paul (World Bank, Washington, DC, 2019)
This paper investigates a women's self-help group program with more than 1.5 million participants in one of the poorest rural areas of Northern India. The program has four streams of activity in micro-savings, agricultural enterprise training, health and nutrition education, and political participation. The paper considers whether there is any evidence that program membership is associated with quality of life improvement. Using new data on a variety of self-reported capability indicators from members and non-members, the paper estimates propensity score matching models and reports evidence of differences in some dimensions as well as significant benefits to those from the most disadvantaged groups—scheduled castes and tribes. The paper considers robustness and concludes that for some dimensions, there is evidence that the program has contributed to sustainable development through improvements in the quality of life.